2019
DOI: 10.15376/biores.14.4.7664-7674
|View full text |Cite
|
Sign up to set email alerts
|

Screening and optimization of submerged fermentation of lipolytic Aspergillus oryzae

Abstract: Lipases are enzymes commonly used in industry. This study describes the production of lipolytic enzyme via a newly isolated strain of Aspergillus oryzae under a submerged fermentation process. Five strains of A. oryzae were isolated from oil-contaminated soil and water as well as dead decaying organic matter. Qualitative screening revealed that A. oryzae RBM4 strain was a lipase producer, and the process was optimized for enhanced production. Incubation time, incubation temperature, initial pH, use of agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Lipases are commonly applied in food products to enhance both aroma and flavor of cheese, yogurt, milk, and butter (Iftikhar et al 2011 ). Ahmed et al ( 2019 ) reported lipase production by A. oryzae on a variety of lignocellulolytic materials (wheat bran, sorghum, rice bran, wheat straw, corn cobs).…”
Section: A Oryzae As a Biotechnological Tool For Industrial ...mentioning
confidence: 99%
“…Lipases are commonly applied in food products to enhance both aroma and flavor of cheese, yogurt, milk, and butter (Iftikhar et al 2011 ). Ahmed et al ( 2019 ) reported lipase production by A. oryzae on a variety of lignocellulolytic materials (wheat bran, sorghum, rice bran, wheat straw, corn cobs).…”
Section: A Oryzae As a Biotechnological Tool For Industrial ...mentioning
confidence: 99%